Lenses on reading an introduction to theories and models - Tracey, Diane H. (Guilford Press, 2006)
Provides a survey of the major theories and models that influence reading instruction and research. This book helps readers learn why theory matters in designing and implementing high-quality instruction; and how to critically evaluate the assumptions and beliefs that guide their own work with students. It is useful for graduate students.